Wild plants and fungi sold in the markets of Yerevan (Armenia) - Siranush Nanagulyan; Narine Zakaryan; Nune Kartashyan; Renata Piwowarczyk; Łukasz Łuczaj (BMC, 2020)
Abstract Background The aim of the study was to record wild plants and fungi sold in the capital of Armenia. This is the first large market survey in the Caucasus region. The area of the Caucasus is characterised by a very high diversity of climates, flora and languages which results in very rich traditions of plant use. Methods Interviews were conducted and photos and voucher specimens were taken during multiple visits made over 4 years. We studied 37 locations and 136 people were interviewed. Results As many as 163 plant species, belonging to 44 families and 110 genera, were recorded on Yerevan markets. This included 148 wild food species, 136 medicinal species, 45 species sold for decoration, 15 species of wood and 9 species of insect repellents. Also 14 wild species of fungi were sold, including 12 food species. Conclusions The list of plants sold in the markets of Yerevan is very extensive and diverse, and includes many species of wild fruits, vegetables and medicinal plants, some of them never listed in ethnobotanical directories before. A characteristic feature of this market is a large representation of lacto-fermented products. Some of the species sold in Yerevan have never been reported as human food either in wild edible plant word lists or in ethnobotanical publications, e.g. Angelica tatianae, Ferulago setifolia and Heracleum chorodanum. Fungi are also well represented.